Malaysian small and medium industries (SMIs): Priority and model of product design process - Saud, Mohammad Basir; Md Isa, Mohd Azwardi; Mohd Saifudin, Adam (2009)
The main purpose of this paper is to explore, identify, and prioritise the factors and product attributes considered by Malaysian Small and Medium Industries (SMIs) when designing and redesigning their products, and in managing their companies design process.The core data and information were gathered through a survey (mailed questionnaires) from a total of 137 respondents of Malaysian SMIs and a programme of semi-structured interviews from 28 managers of Malaysian SMI's (though additional interviews were also conducted). The findings of the study revealed that Malaysian SMIs are generally not effective in designing products for the export market.The study also revealed that the effectiveness in the product design process is better integrated through cross-functionally team. In addition, the findings and discussed contained in this study have resulted in proposing a model of the product design process. Finally, the researcher has several prioritised recommendations for practitioners and suggestions have been highlighted for the future researchers, government and its agencies, and policy makers.